PENINGKATAN KEAKTIFAN DAN PENGUASAAN MATERI MELALUI PENGEMBANGAN MODEL PEMBELAJARAN - Yuliantoro; Supentri; Yanuar Al Fiqri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research utilized a quantitative approach with a descriptive observational method aiming to increase students' activeness and mastery of the material. Data were collected through observation, documentation, and reference studies related to learning. The study focused on observing the implementation of learning to assess students' activeness and the improvement of material mastery through several learning models. The results showed that learning activities designed to stimulate all students’ senses during the learning process successfully increased students’ activeness. Initial assessments measuring material mastery without using a learning model showed an average score of 68%, which was close to a good category. However, when treated with the spider webs and walking sticks models in discussion activities, learning became more engaging, resulting in an average material mastery score of 90%, indicating a very good category.